Island and Rensch’s rules do not apply to cave vs. surface populations of Asellus aquaticus - Herczeg, Gábor; Balázs, Gergely; Biró, Anna; Fišer, Žiga; Kralj-Fišer, Simona; Fišer, Cene (Frontiers in Ecology and Evolution, 2023)
Body size is a trait of fundamental ecological and evolutionary importance that is often different between males and females (sexual size dimorphism; SSD). The island rule predicts that small-bodied species tend to evolve larger following a release from interspecific competition and predation in insular environments. According to Rensch’s rule, male body size relative to female body size increases with increasing mean body size. This allometric body size – SSD scaling is explained by male-driven body size evolution. These ecogeographical rules are rarely tested within species, and has not been addressed in a cave – surface context, even though caves represent insular environments (small and isolated with simple communities). By analyzing six cave and nine surface populations of the widespread, primarily surface-dwelling freshwater isopod Asellus aquaticus with male-biased SSD, we tested whether cave populations evolved larger and showed higher SSD than the surface populations. We found extensive between-population variation in body size (maximum divergence being 74%) and SSD (males being 15-50% larger than females). However, habitat type did not explain the body size and SSD variation and we could not reject isometry in the male – female body size relationship. Hence, we found no support for the island or Rensch’s rules. We conclude that local selective forces stemming from environmental factors other than island vs. mainland or the general surface vs. cave characteristics are responsible for the reported population variation.